2022
DOI: 10.1186/s12893-022-01804-8
|View full text |Cite
|
Sign up to set email alerts
|

3D-printed hemipelvic prosthesis combined with a dual mobility bearing in patients with primary malignant neoplasm involving the acetabulum: clinical outcomes and finite element analysis

Abstract: Background Limb salvage reconstruction for pelvic tumors, especially periacetabular tumors, is challenging. We combined the use of dual mobility bearing and 3D-printed hemipelvic prosthesis to improve function and reduce the probability of complications after hemi-pelvic resection in patients with primary acetabular malignancy. The purpose of this study was to evaluate the efficacy and safety of this combination. Methods Between October 2011 and Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Furthermore, the gait cycle in the present study was adopted from Paul 35 with quasistatic force at specific time points to simplify the computational configuration. Dynamic force at the complete cycle is required to obtain more realistically accurate contact pressure results on dual-mobility hip joint prostheses 49,50 . Finally, the present results were only validated by Gao et al 31,37 on computational simulation results on single-and dual-mobility hip joint prostheses, but a comparison with corresponding experiments was not performed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the gait cycle in the present study was adopted from Paul 35 with quasistatic force at specific time points to simplify the computational configuration. Dynamic force at the complete cycle is required to obtain more realistically accurate contact pressure results on dual-mobility hip joint prostheses 49,50 . Finally, the present results were only validated by Gao et al 31,37 on computational simulation results on single-and dual-mobility hip joint prostheses, but a comparison with corresponding experiments was not performed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, computer technology and advanced manufacturing have witnessed rapid development, and 3D printing technology is widely applied for orthopedic trauma for exactly contouring reconstruction plates 8,20–22 . By using the 3D printing‐based pre‐contoured plate for acetabular fracture reduction and plate fixation, Wang et al 22 pointed out that the surgery had less blood loss and shorter surgical time.…”
Section: Discussionmentioning
confidence: 99%
“…8,[10][11][12]19 In recent years, computer technology and advanced manufacturing have witnessed rapid development, and 3D printing technology is widely applied for orthopedic trauma for exactly contouring reconstruction plates. 8,[20][21][22] By using the 3D printing-based pre-contoured plate for acetabular fracture reduction and plate fixation, Wang et al 22 pointed out that the surgery had less blood loss and shorter surgical time. Compared with traditional intraoperative contouring, Chen et al 10 indicated that there were better clinical outcomes through the application of 3D printing technology and pre-contoured reconstruction plates in acetabular fracture surgery.…”
Section: The Advantages Of Patient-specific Pre-contoured Plate Fixat...mentioning
confidence: 99%
“…The four models were subjected to bipedal standing (Control, Model 1–3_B), and the femoral neck of the healthy and reconstructed sides was constrained symmetrically. An axial load of 2,000 N was imposed on the center of the artificial acetabulum in Model 3 (Model 3_E) to mimic the most loaded circumstance in one gait cycle ( Bergmann et al, 2001 ; Wang et al, 2022 ; Zhou et al, 2022 ). In terms of boundary conditions, the area of the upper surface of the L4 vertebral body was considered to be fully bonded ( Figure 2 ).…”
Section: Methodsmentioning
confidence: 99%